1997
DOI: 10.1002/(sici)1099-0488(199710)35:14<2219::aid-polb3>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of crystalline index in nylons by DSC: Complexities and recommendations

Abstract: Differential scanning calorimetry (DSC) is one of the most widely used technique for measuring crystallinity in the polymer industry. The major source of error in the crystalline index (CIDSC) of low crystallinity polymeric articles, is the development of further crystallinity during the DSC scan. Although, this type of cold crystallization is obvious, and thus accounted for in polymers like polyethylene terephthalate, nylons are a difficult class of materials in that respect. The major contributing factors to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(117 citation statements)
references
References 4 publications
4
111
0
2
Order By: Relevance
“…The DSC instrument was calibrated using an Indium standard. The procedure for DSC characterization was adapted from PA66 measurements performed by Khanna and Kuhn (1997). After loading each sample into aluminum autosampler pans and crimping the pans closed, a needle was used to create a small hole in the pan lid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DSC instrument was calibrated using an Indium standard. The procedure for DSC characterization was adapted from PA66 measurements performed by Khanna and Kuhn (1997). After loading each sample into aluminum autosampler pans and crimping the pans closed, a needle was used to create a small hole in the pan lid.…”
Section: Methodsmentioning
confidence: 99%
“…After drying, the pan was immediately put into the DSC for a second drying step in which the sample was heated from 25 to ~55 °C at a rate of 20 °C/min, held for 2 min, and then air-cooled to room temperature. The purpose of the second step was to remove additional water and to allow enthalpic relaxations in the amorphous regions of the polyamide that occur as a result of removing moisture during the initial drying step (Khanna and Kuhn, 1997). Khanna and Kuhn found that relaxation of amorphous material causes uncertainty in the baseline above T g which can lead to incorrect interpretations of crystallinity.…”
Section: Methodsmentioning
confidence: 99%
“…Some authors like Kim et al, [39] and Khanna et al, [40] have attributed this behavior, named "sub-T m " exotherm, to partial melting and recrystallization during the heating run. Some other explanations have been oriented toward an energy relaxation process, which stored during processing.…”
Section: Methodsmentioning
confidence: 99%
“…Como pode ser observada, a introdução da argila altera o formato desses picos, modificando provavelmente a cristalinidade da PA 6. De acordo com Khanna and Khun [21] , a poliamida 6 pode assumir duas formas cristalográficas, monoclínica α e monoclínica ou pseudo-hexagonal γ.…”
Section: Leite a M D Et Al -Obtenção De Membranas Microporosas Aunclassified